Representation of Masculinity in Chinua Aschebe's "The Voter" and Dimas Jayadinekat's "Si Pemalu Menang Pemilu": A Comparative Analysis - Wardhana, Stanislaus Bayu Kusuma (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The social construction of masculinity supports men's dominant roles, the subjugation of both the general male and female population, and other suppressed manifestations of masculinity. To reveal that subtle aspect, this study investigates how masculinity is portrayed in "The Voter" by Chinua Achebe and "Si Pemalu Menang Pemilu" by Dimas Jayadinekat. This study used the social construction of masculinity and hegemonic masculinity by Connell. Since the data took the form of narratives about the short stories, the qualitative descriptive method was used. A close reading technique is used to support the analysis of the data to find evidence. The result shows that there is some evidence of the social construction of masculinity and actions done by the main characters that represent hegemonic masculinity. Even though these short stories have different origins, the construction of masculinity of being an ideal man is relatively similar. It has also shown that masculinity is not simply ‘there’, there must be a construction of masculinity by society as depicted in both short stories.